Penerapan Quality Function Deployment (QFD) pada Pengembangan Produk Sabun di UKM Kota Batam - Sugianto, Welly; Prasetyo, Rony (Jurnal Optimasi Sistem Industri, 2018)
Usaha Kecil Menengah (UKM) Simo was established since 2002 and produces various hygiene products such as detergent soap, bath soap, softener and others. Currently, Simo has a mainstay product in the form of bath soap for the hotel. However, these products still cannot dominate the Batam market. Sales of bath soap are declining. The decline is due to soap products that are made not in accordance with customer expectations. This study looks for product specifications that meet customer expectations. The method used is quality function deployment (QFD). The purpose of this study is to design a quality soap product in accordance with customer expectations. The customer voices are grouped in such a way as to get an overview of customer expectations. The process of grouping is done by using exploratory factor analysis method. Through exploratory factor analysis, the company can get customer expectations that may not be explored through the questionnaire. Through this general overview, customer expectations are detailed up to the tertiary stage. The priority of customer expectations is determined based on the questionnaire data so that the allocation of resources can be done appropriately. Details of these expectations are related to the technical characteristics. Through the technical characteristics, the company is able to make products according to the customer expectations.